Successful management of twin pregnancy in a woman with advanced chronic kidney disease: A case report. Issue 33 (August 2019) - Wei, Yunbo; Wang, Yan; Yao, Qiang; Zhou, Li; Fu, Ping
Abstract: Rationale: Twin pregnancy in women with chronic kidney disease (CKD) is very rare but poses a great risk to both mother and children. In developing countries like China, advanced CKD twin pregnancies are often terminated. Here, we report a successful case and reviewed related cases, hope to facilitate further study. Patient concerns: A 29-year-old woman with a twin pregnancy showed serum creatinine (Scr) 100 μmol/L (CKD2) at conception. During her 12th week, Scr reached 263 μmol/L (CKD4) with urine protein 3+ and hypertension. Diagnoses: Due to her pregnancy, renal biopsy was not considered. Lab tests showed deterioration of renal function and ultrasound detections showed small kidney size. Interventions: The patient was given basic drug therapy to control her blood pressure and supplemental nutrition without hemodialysis. Outcomes: The patient delivered 2 healthy babies weighting 0.9 and 0.7 kg by cesarean section at the 28th week, but has been under maintenance hemodialysis since then. Lessons: Despite low birth weight and preterm delivery, successful twin pregnancies in some patients with CKD could be realized under early multidisciplinary intervention, but this poses great risks for mothers and twins, especially for patients with advanced CKD and those on hemodialysis.